Hierarchical Engineering of Porous P2‐Na2/3Ni1/3Mn2/3O2 Nanofibers Assembled by Nanoparticles Enables Superior Sodium‐Ion Storage Cathodes. (27th November 2019) - Liu, Yongchang; Shen, Qiuyu; Zhao, Xudong; Zhang, Jian; Liu, Xiaobin; Wang, Tianshi; Zhang, Ning; Jiao, Lifang; Chen, Jun; Fan, Li‐Zhen
Abstract: Layered transition metal oxides (TMOs) are appealing cathode candidates for sodium‐ion batteries (SIBs) by virtue of their facile 2D Na + diffusion paths and high theoretical capacities but suffer from poor cycling stability. Herein, taking P2‐type Na2/3 Ni1/3 Mn2/3 O2 as an example, it is demonstrated that the hierarchical engineering of porous nanofibers assembled by nanoparticles can effectively boost the reaction kinetics and stabilize the structure. The P2‐Na2/3 Ni1/3 Mn2/3 O2 nanofibers exhibit exceptional rate capability (166.7 mA h g −1 at 0.1 C with 73.4 mA h g −1 at 20 C) and significantly improved cycle life (≈81% capacity retention after 500 cycles) as cathode materials for SIBs. The highly reversible structure evolution and Ni/Mn valence change during sodium insertion/extraction are verified by in operando X‐ray diffraction and ex situ X‐ray photoelectron spectroscopy, respectively. The facilitated electrode process kinetics are demonstrated by an additional study using the electrochemical measurements and density functional theory computations. More impressively, the prototype Na‐ion full battery built with a Na2/3 Ni1/3 Mn2/3 O2 nanofibers cathode and hard carbon anode delivers a promising energy density of 212.5 Wh kg −1 . The concept of designing a fibrous framework composed of small nanograins offers a new and generally applicable strategy for enhancing the Na‐storage performance of layered TMO cathode materials. Abstract : Porous P2‐Na2/3 Ni1/3 Mn2/3 O2 nanofibers assembled by nanoparticles effectively facilitate the reaction kinetics and stabilize the structure as cathode materials for sodium‐ion batteries. Upon repetitive sodiation/desodiation, the rapid Na + diffusivity with a low ionic migration barrier is responsible for the high rate capability, the highly reversible structure evolution and Ni/Mn valence change are responsible for the high cyclic stability.